Association Of Severity of Anemia and Depression Among Patients Presenting with Oral Ulceration - Afifa Razi; Atif Iqbal Butt; Saima Qureshi; Iqra Akram; Aeman Ali; Ayesha Saghir; Nosheen Nazir (KARACHI MEDICAL AND DENTAL COLLEGE, 2021)
Objective: To determine the association of severity of anemia with depression among patients presenting with oral ulceration at Ziauddin University Dental OPD, Karachi, Pakistan. Materials and methods: It was an observational study conducted at the department of oral medicine and diagnosis of Ziauddin College of dentistry, Karachi, Pakistan for the duration of one year. One sixty one patients of age 20-50 years of either gender presenting with active aphthous stomatitis (burning sensation on NRS?2 and pain on NRS?3) from last 3-6 months were included in the study using non-probability consecutive sampling technique. All the patients were assessed for depression using Patient Health Questionnaire Depression Scale (PHQ-9) and anemia using CBC. PHQ-9 score?5 was deemed as depression positive and the hemoglobin (Hb) level less than 13 g/dL for men and less than 12 g/dL for women was deemed as anemia. Data regarding demographics along with characteristics of oral ulcerations were also noted on pre-designed proforma. SPSS version 23 was used to analyze data. Results: Out of 161 patients with oral ulcers, depression was prevalent in 69%. About 37% of the patients were moderately anemic, 32% were severely anemic and 31% had mild anemia. The significant association was found between depression and severity of anemia (p=0.028). The factor such as age?35 years, female sex and multiple ulcer lesions among anemic and depressed patients were found statistically significant (p<0.05). Conclusion: The study concluded that depression and anemia are significantly correlated and can increase the incidence of oral ulceration. Keywords: Oral ulcer, aphthous ulceration, recurrent aphthous stomatitis, depression, anemia, hemoglobin level